Institutional Influence, Transition Management and the Demand for Carbon Auditing: The Chinese Experience. Issue 2 (30th March 2018) - Tang, Qingliang
Abstract: The primary objective of this study is to investigate factors associated with the increase in demand for carbon auditing in China. Based on an analysis of publicly available carbon‐related information and data, the paper documents the large amount of carbon auditing that occurred in the public sector during the period 2009–2013. We find that the creation of carbon institutions and the significant increase in governmental green funding were the main reasons for the emergence of carbon auditing in this period. The change in models of economic development attempting to balance GDP growth and ecosystem protection, in addition to institutional reform, has led carbon auditing from rhetoric to practice. In addition, we show that carbon auditing serves as a tool for the management of transitions and the governance of sustainable socio‐technical and organisational innovation and transformation. Abstract : Through an analysis of publicly available carbon‐related information and data, this study investigates factors associated with the increase in demand for carbon auditing in China. The paper finds that the creation of carbon institutions and the significant increase in governmental green funding are the main reasons for the emergence of carbon auditing during the period 2009–2013.